Acceptance and application of Islamic financial planning among small and medium enterprises Halal operator in Peninsular of Malaysia - Awang, Mohd Daud; Mohd Noor, Muhamad Nur Aiman; Muhammad, Junaina; Abdullah, Amalina; Ab. Rahman, Suhaimi; Yahya, Mohamed Hisham (International Organization Center of Academic Research, 2016)
Halal Industry in Malaysia has created employment opportunities especially among Small, medium-sized enterprises (SMEs). High demand for Halal products especially from Islamic countries has put Halal industry as one of the national agenda priorities. In the Eleventh Malaysia Plan (11MP), the halal industry had been given special emphasis by the Prime Minister to ensuring the halal industry is highly and persistently competitive. In Asia, Malaysia has been considered as a leader in the development of the Halal hub center. However, halal industry is not only about halal food production, but also it covers Islamic finance services which prohibit interest (riba), uncertainties (gharar) and gambling (maysir). Islamic financial planning is one of the important parts of Islamic finance because it plays a big role in providing Shariah compliant funds and investment opportunities especially for SMEs halal operators. The holistic approach to halal industry should also cover not only halal food production, but also Islamic financial planning which includes activities such as how to create, increase, purify and to protect wealth from Islamic perspective. Therefore, this study examines the relationship between acceptance of Islamic finance and the application of Islamic financial planning among SMEs halal operators in Peninsular Malaysia. The findings of this study reveal that the acceptance of Islamic finance was significantly correlated with the application of Islamic financial planning among SMEs halal operator. These finding indicated the important of integration between acceptance on the Halal industry with Islamic financial planning activities. SMEs Halal operators should be able to accept the Islamic finance principles. This relationship recognises the importance of acceptance and practice of Islamic financial planning among halal SMEs operators in promoting halal products and services and boost demand for Malaysian halal products at the international level.